Synthesis of benzo[d]imidazo[2,1-b]benzoselenoazoles: Cs2CO3-mediated cyclization of 1-(2-bromoaryl)benzimidazoles with selenium - Matsumura, Mio; Kitamura, Yuki; Yamauchi, Arisa; Kanazawa, Yoshitaka; Murata, Yuki; Hyodo, Tadashi; Yamaguchi, Kentaro; Yasuike, Shuji (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of benzimidazo[2,1-b]benzoselenoazoles is described. The novel ring-closure reaction of 1-(2-bromoaryl)benzimidazoles with Se powder is promoted by Cs2CO3 (2 equiv) in DMF at 150 °C. Moreover, the obtained tetracyclic heterocycles are all novel compounds. Single-crystal X-ray analysis of the parent benzimidazo[2,1-b]benzoselenoazole revealed that the tetracyclic ring is almost planar. Absorption spectroscopy data of the benzimidazo[2,1-b]benzoselenoazoles showed the λmax was dependent on the number of rings.
Keywords: benzimidazole; cesium carbonate; cyclization; selenium; selenoazole